Interinformant agreement of the dementia questionnaire for people with learning disabilities. (8th August 2014) - Walker, Brigid; MacBryer, Shona; Jones, Alan; Law, Jim
<x xml:space="preserve">Abstract</x> Accessible summary Many services use carer questionnaires to decide whether people with Down's syndrome are developing dementia. Using one of these questionnaires (the DLD), we looked at how well carers agreed with each other. Only 15% of carers achieved 'good' agreement. Carers agreed more with each other when rating people who are less able. This backs up recommendations not to rely only on carer interviews when assessing for dementia. Summary Because of difficulties with neuropsychological assessments for dementia in people with learning disabilities, professionals in clinical practice have relied heavily on carer interviews, one of the most widely used being the Dementia Questionnaire for People with Learning Disabilities (DLD – Evenhuis et al. 2006 Dementia questionnaire for people with intellectual disabilities manual (second edition). Amsterdam, Netherlands, Harcourt Test Publishers). Because dementia is indicated by the magnitude of changes in scores between longitudinal assessments, interinformant agreement is paramount. We carried out the DLD interview independently with two carers for each of 26 people with Down's syndrome. Only 15% of pairs of carers achieved 'good' agreement. Levels of agreement varied widely across the DLD subscales and individual questions. Interinformant agreement was better for less able people with Down's syndrome than for more able individuals.